The Long-Run Effects of Immigration: Evidence across a Barrier to Refugee Settlement - Antonio Ciccone; Jan Sebastian Nimczik (Institute of Labor Economics (IZA), 2022)
After the end of World War II in 1945, millions of refugees arrived in what in 1949 became the Federal Republic of Germany. We examine their effect on today's productivity, wages, income, rents, education, and population density at the municipality level. Our identification strategy is based on a spatial discontinuity in refugee settlement at the border between the French and US occupation zones in the South-West of post-war Germany. These occupation zones were established in 1945 and dissolved in 1949. The spatial discontinuity arose because the US zone admitted refugees during the 1945-1949 occupation period whereas the French zone restricted access. By 1950, refugee settlement had raised population density on the former US side of the 1945-1949 border significantly above density on the former French side. Before the war, there never had been significant differences in population density. The higher density on the former US side persists entirely in 2020 and coincides with higher rents as well as higher productivity, wages, and education levels. We examine whether today's economic differences across the former border are the result of the difference in refugee admission; the legacy of other policy differences between the 1945-1949 occupation zones; or the consequence of socio-economic differences predating WWII. Taken together, our results indicate that today's economic differences are the result of agglomeration effects triggered by the arrival of refugees in the former US zone. We estimate that exposure to the arrival of refugees raised income per capita by around 13% and hourly wages by around 10%.
Keywords: O4; O11; R11; 330; immigration; productivity; wages; refugees; long-run effects